The Impact of Plastic Waste on Passo Beach Pollution in RT. 019/RW. 004 Passo Village, Baguala District, Ambon City - Luturmas, Wendi Welem; Sihasale, Daniel Antoni; Riry, Roberth Berthy (Jurnal Pendidikan Geografi Unpatti, 2023)
This study aims to determine the impact of plastic waste on coastal pollution and test the water quality to better understand the pollution due to plastic waste in RT 019 / RW 04 Passo Village, Baguala District, Ambon City. The benefits of the study are expected to provide knowledge that with the presence of researchers looking at the severe problems that occur on Passo Beach, both the physical impacts that occur, there needs to be a review by the government or Ambon City Government to take preventive measures both for the community of RT 019 / RW 004 or the community as a whole living on the coast of Pasi Beach so that the beach remains clean and the community remains healthy. The type of research used in this study is qualitative descriptive research, namely, describing the impact of plastic waste on Passo Beach pollution in RT.019 / RW. 004. The results of the study showed that the single variable, namely the impact of plastic waste on coastal pollution with its indicators as Quality Indicators consisting of Physical parameters (Odor, Total Dissolved Solids (TDS), Turbidity, Taste, Temperature, Color). Chemical (Arsenic, Fluoride, Total Chromium, Cadmium, Nitrite, Nitrate, Cyanide, Selenium, Iron, Hardness, Chloride, Manganese, pH, Zinc, Sulfate, Lead), and Total Coliform Biology.